Determining pH by CEDST MRI - ALETRAS, ANTHONY H; BALABAN, ROBERT S; WARD, KATHLEEN M (2009)
A method for obtaining an image by MRI, comprising: administering at least one contrast agent to a subject min amounts effective to perform CEDST MRI analysis; and performing DEDST MRI analysis to produce an image of the subject. A number of different contrast agents can be used to practice the present method including, without limitation, sugars, amino acids, nitrogen-containing heterocycles, purines and pyrimidines, nucleosides; imidazole and derivatives thereof, amino acids, barbituric acid and analogs thereof, and miscellaneous materials, such as guanidine hydantoin, parabanic acid, and biologically active salts thereof.